Career counselling models and services for students with specific learning disabilities - Chiedu Eseadi (KONSELOR, 2023)
The exploration of students' potential and learning capacities may provide deeper insights into their characteristics and serve as a foundation for providing practical career guidance, especially for those with specific learning disabilities (SLDs). This article presents an examination of career counselling models and services for students with SLDs. The chosen methodology for this research was a narrative literature review. Some examples of career counselling models discussed in this article include the trait-and-factor model, the client-centered career counselling model, and the faith-based career counselling model. The provision of career counselling services to students with SLDs was addressed, including aspects such as choosing a career and promoting a balance between their professional and personal lives. Career counselling models provide counsellors with a practical framework for implementing career counselling with students. These models are particularly valuable in offering practical career assistance to students with SLDs. It is advisable for career counsellors to acquire a deeper understanding of the experiential worldviews held by students with specific learning disabilities, recognise the potential impact of these disabilities on students' sense of self, and formulate interventions aimed at facilitating these students' adaptation to the educational environment and professional settings. Students with specific SLDs who use career counselling services are afforded the chance to develop a professional identity that is in congruence with the demands of the current job market.